Portable IoT Connected Device for Vibration and Temperature Measurement - Azamataufiq Budiprasojo; Risse Entikaria Rachmanita; Mochamad Irwan Nari (Nusantara Science and Technology Proceedings, 2022)
This study aims to design of portable IoT-connected device for vibration and temperature measurements that are installed on a wind turbine gearbox. The device consists of a battery 7.4 volt 6800 mAh, Arduino ESP32, sensor DHT22, sensor ADXL345, buzzer, SD card, connected to laptop and wifi. The device is placed in a wind turbine gearbox that is run at 220 rpm and a frequency of 15 Hz and is tested for 3 minutes. The first minute was under normal conditions, the second minute by giving vibration to the gearbox and the third minute normalized again the test results show that the treatment affects temperature, humidity, and acceleration on the x, y, and z axes of the gearbox. As a result of the treatment by giving vibration to the gearbox, the temperature increases, the humidity decreases, the acceleration of the x-axis increases, and the acceleration of the y-axis and the z-axis decreases.